Penerapan Model Pembelajaran Problem Based Learning dengan Media Audio Visual terhadap Hasil Belajar Siswa: The Application of Problem-Based Learning Models with Audio-Visual Media to Student Learning Outcomes - Ghaifira Husna Putri; Nafisah Hanim; Eva Nauli Taib; Zuraidah Zuraidah; Elita Agustina (ITScience (Information Technology and Science), 2025)
Learning outcomes reflect the evaluative results of learning activities, which indicate that the learning process is effective if accompanied by changes in behaviour, competence, and mastery of student information. Factors influencing learning success include individual capacity, motivation, and environment. Seventh-grade students of MTsN 2 Banda Aceh have poor academic achievement, especially in classifying living things. This study aims to analyse student learning outcomes using the PBL learning model with audiovisual materials to classify living things. The research methodology is a pre-experimental quantitative descriptive method. The teacher has not used various models or media in the learning process to catch up; students only receive information from the teacher without trying to learn independently. The research design is a single-group pretest-posttest. Data were evaluated using the gain normality test, the N-gain formula, and t-test analysis. Statistics show that the average pretest score is 37 and the average posttest score is 83. The high group has an increase in student learning outcomes of 0.72. The t-test analysis showed that the pretest and posttest scores were statistically significantly different, with tcount smaller than ttable (tcount = -24.697 < ttable = 2.030). Using the PBL learning model combined with audiovisual media resources has been proven to improve student learning outcomes at MTsN 2 Banda Aceh significantly.